Kajian eksperimental mekanisme rol pemipih pada prototipe mesin pemipih emping beras - Suhendra Suhendra; Feby Nopriandy; Irma Fahrizal (TURBO [Tulisan Riset Berbasis Online], 2021)
Rice quaker are traditional food from the Sambas regency. The manufacture of rice quaker has been traditionally done by pounding it. Economically, the production capacity of traditionally made rice quaker is so low that it needs to be increased by changing the manual to mechanical flattening system. The purpose of this research is designing a prototype machine for flattening rice quaker as well as conducting experimental studies on the flattening process. The research stages were to design, manufacture, and test the performance of the flattening rice quaker. The independent variables of the study were the gap width and the number of flattening, while the dependent variables of the study were thickness and percentage damage of rice quaker. The width of the gap was varied into 0.4 mm, 0.6 mm, 0.8 mm, and 1.0 mm, while the number of flattening was varied to 1, 2, and 3 times the flattening. The result of the construction of the prototype rice quaker machine is in accordance with the initial design, and can work to flatten rice quaker. The engine test was carried out at a flat roller speed of 360 rpm. The thickness of the rice quaker made traditionally, 0.98 mm, can be approached by flattening using a machine at a gap width of 0.8 mm with 2 flakes resulting in a thickness of 0.96 mm quaker with a percentage of damage of 38.52%. In general, the level of damage to the resulting rice quaker is still very high, so further analysis is needed.Keywords: Rice quaker, gap width, flattening machine, flat rollers.